A questão da autodidaxia em educação e seus fundamentos nas filosofias de Kant e de Heidegger - Yukizaki, Suemy (1991)
Free will, taken here as the kind of independence every human being develops in his growth process, can not be restricted, also in the field of education, to the affirmation of some vague and relative autonomy, characteristic of any social process. To try to find its philosophical basis, in the hope of finding more precise determinants of its possibility, is a must for those who want to escape certain ideological ambiguity, which is manifested, on the one hand, in the incorporation of natural phenomena to the social field and, on the other hand, in the praising of what is inherent to human essence: the ability of constructing humanity in the process of social formation. Both Kant and Heidegger -each in his own way, but never mutually exclusive - allow us to give formative autonomy philosophical foundations, through the category of transcendence. In Kant, freedom, understood as the possibility man has - since it is inscribed in the range of humanity - to innaugurate a totally original action, bypassing the cause-consequence mechanism inherent to natural phenomena; in Heidegger, the innauguration of the pre-sence man's ontological entity - that allows him to constitute humanity together with the construction/revelation of the world, are the basis for that which we call free will. Bachelard, by incentivating material imagination, joins those two philosophers and promotes the commitment of the pedagogical praxis to formative autonomy. By insisting on the material nature of action, material imagination renews all aquired knowledge and reintroduces the question of formation, thus retrieving the possibility of self-formation. Material imagination, therefore, asserts itself as object of pedagogical praxis and, at the same time, reveals itself to be the finish of its own methods.